Co3O4 Electrode Prepared by Using Metal-Organic Framework as a Host for Supercapacitors. (17th March 2015) - Jiang, Jiaqiang; Wei, Fuxiang; Yu, Genxi; Sui, Yanwei
Abstract : Co3 O4 nanoparticles were prepared from cobalt nitrate that was accommodated in the pores of a metal-organic framework (MOF) ZIF-8 (Zn(MeIM)2, MeIM = 2-methylimidazole) by using a simple liquid-phase method. Analysis by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) showed that the obtained Co3 O4 was composed of separate nanoparticles with a mean size of 30 nm. The obtained Co3 O4 nanoparticles exhibited superior electrochemical property. Co3 O4 electrode exhibited a maximum specific capacitance of 189.1 F g −1 at the specific current of 0.2 A g −1 . Meanwhile, the Co3 O4 electrode possessed the high specific capacitance retention ratio at the current density ranging from 0.2 to 1.0 A g −1, thereby indicating that Co3 O4 electrode suited high-rate charge/discharge.